Deposition and Evaluation of Mn-Co Oxide Protective Sputtered Coating on SOFC Interconnects and Current Collectors. Issue 8 (14th June 2016) - Kumar, S. Senthil; Nalluri, Abhishek; Anandan, C.; Prakash, B. Shri; Aruna, S. T.
Abstract : Ferritic stainless steel (FSS) is a prospective interconnect material for use in solid oxide fuel cells (SOFCs). However, the performance of the metallic interconnect deteriorates in the typical operating condition of SOFC due to oxide scale growth. To overcome this problem, Mn-Co oxide has been investigated as a protective coating for SOFC bi-polar plates. Similarly, protective oxide coated FSS mesh has been fabricated and explored for cathode current collection to replace the expensive Pt mesh. In the present study, Mn-Co oxide coating has been developed by sputtering technique using target fabricated by uniaxial pressing of solution combustion synthesized powder. The synthesized powder has been characterized for particle size, composition and morphology. The target is also characterized for phase and crystal structure. Sputtering conditions are optimized to get an adherent coating on SS430 substrates and meshes. The coating displays good oxidation resistance with reasonable electrical conductivity. Significant improvement in oxidation resistance is observed for the sputtered Co-Mn perovskite type oxide coating. Co-efficient of thermal expansion of the formed perovskite phase is established. Further, the stability of Co-Mn perovskite oxide phase after 72 h of oxidation is investigated by analyzing the phase. The current collector mesh with protective coating exhibits a stable area specific resistance (ASR) indicating the potential of this coating for wide range of SOFC applications including Intermediate Temperature (IT) SOFC. Also, the present work establishes solution combustion method as a viable approach to prepare targets for sputtering.